STRATEGIC MANAGEMENT OF THE PRINCIPAL IN MANAGING EXCELLENT PROGRAMS AT SMK HASAN JUFRI BAWEAN - Ana Luthfia Putri Awaliyah (JOURNAL OF HUMANITIES AND SOCIAL STUDIES, 2024)
Based on the background, the implementation of strategy in management involves great efforts in transforming the strategic objectives, namely the implementation of school education programs. Therefore, the ability of school principals and other school personnel to implement a strategy in educational management is the most important thing related to skills as leaders and teachers as professionals. The research focus in this study is what is the principal's strategy in managing the education program at Hasan Jufri Bawean Vocational School? and what are the implications of the principal's strategy in managing the education program at Hasan Jufri Bawean Vocational School. The aim is to find out how the principal's strategy is in managing superior programs and the implications of the principal in managing superior programs at Hasan Jufri Bawean Vocational School. This research uses strategic management theory, principal theory, leadership theory, and superior program theory. This research uses a qualitative approach by looking for meaning based on data sources using field research, this research was conducted at Hasan Jufri Bawean Vocational School, data collection through a structured interview process, observation and documentation, data analysis method using descriptive analysis method, namely a data analysis method that describes or describes the state of the research object. The validity of the data uses triangulation by combining several existing data collection techniques and data sources. The school has two vocations, namely Marine Fishing Nauticals (NKPI) and Institutional Financial Accounting vocations (AKL). Has several superior programs. Like the program, it is required to carry out pakerin (industrial work practices) or known as PKL. The PKL program is implemented when students are in class XI. This is a mandatory program that must be followed by every student, for 6 months. The location of the PKL depends on each major, for the AKL (Institutional Financial Accounting) major, it is usually located at BMT Sidogiri, Mitra Bank, Pegadaian, Hospital and so on. For the NKPI (Nautics Marine Fishing) event, it is located at the sahbandar, Bawean Harbor, Lamongan Harbor and BMKG. Because the school does not yet have cooperation with any company. The implications of implementing the principal's management strategy at Hasan Jufri Bawean Vocational School are proven by the presence of alumni who work in several company installations. The principal of Hasan Jufri Bawean Vocational School is collaborating with the Gresik district BKK (Special Job Exchange) where all information related to job vacancies will be conveyed to Hasan Jufri Bawean Vocational High School (SMK) alumni. With the hope that all alumni can get jobs in their respective fields.